Breaking the rules of ethics in journalists’ posts on Twitter - Gwioździk, Magdalena; Płaczkiewicz, Karol (Zjawiska propagandy i manipulacji w prasie, telewizji, radiu i Internecie, 2022)
The aim of the paper is to describe examples of violations and breaches of journalistic ethics committed by polish writers. Using examples of Twitter posts published by polish journalists and referring to the Media Ethics Charter, created by the Polish Journalists Association, we will present communicative behaviours, which glaringly violate and breach rules of netiquette as well as ethics of journalism and language. In the article we will use selected posts published by Rafał Ziemkiewicz - journalist, publicist, co-creator of Endecja association, and Konrad Piasecki – TV and radio broadcaster, titled the Journalist of the Year 2015. Twitter is a platform for exchanging views and it is characterised by the use of colloquial rather than formal language. Arguments between users are a common occurrence and public figures – including journalists, who notoriously use eristic tactics - often get involved. The article will talk about the ethics of language, which require respect for the interlocutor, willingness to listen and to conduct (or engage in) a constructive dialogue and are applicable in interactive exchange of views. Selected posts will showcase violations and breaches of those rules, as well as methods of persuasion and manipulation used by the two journalists.